2010
DOI: 10.1161/hypertensionaha.109.139519
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal Repression Between MicroRNA-133 and Calcineurin Regulates Cardiac Hypertrophy

Abstract: Abstract-Cardiac hypertrophy involves a remodeling process of the heart in response to diverse pathological stimuli. Both calcineurin/nuclear factor of activated T cells pathway and microRNA-133 (miR-133) have been shown to play a critical role in cardiac hypertrophy. It has been recognized that the expression and activity of calcineurin increases and miR-133 expression decreases in the hypertrophic heart, and inhibition of calcineurin or increase of miR-133 expression protects against cardiac hypertrophy. mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
115
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 138 publications
(117 citation statements)
references
References 21 publications
(20 reference statements)
2
115
0
Order By: Relevance
“…Mechanically, down‐regulated miR‐30a can aggravate pressure overload‐induced cardiomyocyte hypertrophy by activating autophagy via inhibiting beclin‐1 and loss of miR‐29 can improve hypertensive cardiac remodelling by deletion of Smad7 180. Furthermore, miR‐133 plays a key role in VSMC phenotypic conversion in vitro and in vivo via repressing Sp‐1 and patients with a lower miR‐133 level appear to be more likely to develop or progress to atherosclerosis and cardiac hypertrophy 180, 182. However, further studies are required to better understand the exact function of other miRNAs in regulating the pathogenesis of hypertension.…”
Section: Clinical Value Of Mirnas As New Biomarkers For Angiogenesis‐mentioning
confidence: 99%
“…Mechanically, down‐regulated miR‐30a can aggravate pressure overload‐induced cardiomyocyte hypertrophy by activating autophagy via inhibiting beclin‐1 and loss of miR‐29 can improve hypertensive cardiac remodelling by deletion of Smad7 180. Furthermore, miR‐133 plays a key role in VSMC phenotypic conversion in vitro and in vivo via repressing Sp‐1 and patients with a lower miR‐133 level appear to be more likely to develop or progress to atherosclerosis and cardiac hypertrophy 180, 182. However, further studies are required to better understand the exact function of other miRNAs in regulating the pathogenesis of hypertension.…”
Section: Clinical Value Of Mirnas As New Biomarkers For Angiogenesis‐mentioning
confidence: 99%
“…Cardiomyocytes were prepared for immunocytochemistry as described previously. 7 Detailed information is described in the online-only Data Supplement.…”
Section: Ang Ii-induced Cardiomyocyte Hypertrophy In Vitromentioning
confidence: 99%
“…Overall, these results indicated that MMP-9 may be a direct target of miR-133a in vitro. Discussion miR-133 is an miRNA family containing miR-133a and miR-133b; which differ by only one base in the terminal 3' position (33). miR-133a is a multicopy gene, with two copies in chromosomes 18 and 20, which are located next to another muscle-enriched miRNA, miR-1, while miR-133b is located in chromosome 6 (34).…”
Section: Mmp-9 Is a Direct Target Gene Of Mir-133a In Hccmentioning
confidence: 99%